Optimizing Interdisciplinary Collaboration in the Operating Room: A Comprehensive Exploration of Evolving Surgical Practices - Naif Eid Alzahrani,Talaat Abdulhameed Mohammed, Ismail Sadakah Kirallah, Hamed Mohammed Ali Fattah, Hussain Ali Alqurashi, Adnan Ali Alsulami, Khalid Abdullah Alosaimi,,Badr Dakheeluallah Althgafi,Alaa Abdullah Khotani,Hani Mohammad Konkar,Nabeel Marzoog (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This scientific paper delves into the intricate dynamics of interdisciplinary collaboration within the operating room, focusing on the integration of operation room technicians, nurses, and laboratory specialists. The paper begins with a thorough literature review, encompassing key studies on structured nursing communication, discoveries enabling safer care, interprofessional practice, and team training. The practice implications underscore the need for communication training, team initiatives, and cultivating interprofessional collaboration to enhance healthcare team performance. The paper also outlines future research directions, emphasizing in-depth exploration of specific communication practices, longitudinal studies on the effects of team training, and technological integration for improved collaboration. In conclusion, the paper highlights the importance of continuous adaptation and commitment to interdisciplinary collaboration in creating a patient-centered, safe, and high-quality surgical environment aligned with the demands of contemporary healthcare practices.